Saint Petersburg as One of the Key Points in the Development of Eurasian Integration (Евразийская интеграция: экономика, право, политика, 2019)
The article notes a special position of Saint-Petersburg among the other Russian cities on the level of involvement into international organizations activities. It is proved that St. Petersburg can be described as a city with an international status, which is actively involved in the integration processes as at the level of cross-border cooperation, as well as at trans-regional level. The author gives an example of a partnership with Minsk (Belarus), Yerevan (Armenia), Astana (Kazakhstan) and others. It is noted that St. Petersburg was the first subject of the Russian Federation to the “diagonal” cooperation agreements, i. e., agreements in the form of “subject of Russian Federation - a foreign country”.